Sea wave energy transmission behind submerged absorber caissons. (1st January 2015) - Filianoti, Pasquale; Piscopo, Riccardo
Abstract: The REWEC1 is a submerged caisson breakwater for protecting coasts which remains on the seabed typically 2 or 3 m below the sea surface. The breakwater performs an "active" defence, in that it is able to absorb a share of the incident wave energy. The work shows an original method to estimate the energy transmission behind the breakwater, considering both the wave reflection and the energy dissipation due to the wave breaking over the breakwater and the wave energy absorption. Results confirm that the REWEC1 is a good system for protecting coasts. With significant wave heights lower than 2 m, the energy transmission behind the breakwater is limited, thanks to the resonance that maximize the energy absorption by the plant. With higher significant height (>2 m) the energy transmission behind the breakwater remains limited, thanks to the energy dissipation induced by wave breakings over the roof of caissons. Highlights: The performance of an absorber caisson breakwater for coast defense are investigated. A method for estimating the energy transmitted behind the breakwater is presented. All phenomena involved in the wave-structure interaction have been taken in account. Various operating mode of absorber breakwater have been investigated. A comparison with the transmission coefficient of a rubble mound breakwater is shown.